Malignant focal liver lesions - Hassan, Radhiana (2020)
A lecture on ultrasound features of malignant liver lesion as part of workshop on ultrasound liver, gallbladder and spleen. The topic discussed includes hepatocellular carcinoma, cholangiocarcinoma, hepatoblastoma and liver metastasis.